Istikmal al Turuq al-Taqldiyya: Dirasa Tajribiyya li-Turuq al-Tawhid fi Ta'allum al-Qur'an al-Karim fi al-Manzil Tahfiz al-Qur'an al-Hajj Sanardi - Wahyu, Muhammad; Harahap, Elly Warnisyah (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This article aims to make a new contribution in learning to read the al-Qur’an from generally known methods, namely the Iqra, Baghdadi and Albarqy methods, that each of these methods has its uniqueness, advantages and disadvantages. Therefore, methods are needed to complement each other. What are the steps in applying the method that can be understood easily, clearly and holistically. To answer this, the research method used is an experimental study by identifying each uniqueness, weakness and superiority of existing methods, then analyzing and applying them in several class categories, namely the mubtadi class, mutawassith and tahfidz classes, analyzed descriptively-analytically to draw a conclusion. The experimental study was implemented during January-December 2023. A conclusion was drawn that the unification method applied in H. Sunardi's RTQ (Rumah Tahfidz al-Qur’an) showed adaptation and new contributions by combining the three existing methods. This research confirmed that the unification method succeeded in making it easier for students to introduce the original names of letters, pronounce letter pronunciations and memorize them. gain a deep understanding of recitation, facilitate reading so that teachers can apply it by looking at the cognitive needs of students.